If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (14x + 6y) + (48x + 34y) = 0 Remove parenthesis around (14x + 6y) 14x + 6y + (48x + 34y) = 0 Remove parenthesis around (48x + 34y) 14x + 6y + 48x + 34y = 0 Reorder the terms: 14x + 48x + 6y + 34y = 0 Combine like terms: 14x + 48x = 62x 62x + 6y + 34y = 0 Combine like terms: 6y + 34y = 40y 62x + 40y = 0 Solving 62x + 40y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40y' to each side of the equation. 62x + 40y + -40y = 0 + -40y Combine like terms: 40y + -40y = 0 62x + 0 = 0 + -40y 62x = 0 + -40y Remove the zero: 62x = -40y Divide each side by '62'. x = -0.6451612903y Simplifying x = -0.6451612903y
| 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 | | [2x-6]-4=26 | | v^2=8v+2 | | 4*x=88 | | 3*x-18=2*x^2-18+x^2+3*x+9 | | 5x+12-4x-14=3 | | 5y-10+y+48=5y+40-1y | | 3m+5=2m+3 | | 5xy^2+2x^2+y^3=0 | | 2(t+5)=2 | | 12ab/a^2b^2/3b/2a | | 14-x+2x+5=180 | | h^2+18h+81=0 | | 16x(2)-8x=0 | | 3x+14=-31-6x | | 24=y-7y | | (-6x)(3)= | | 5y-4=3y-2 | | [x+8]-4=12 | | 3x+7=2x+5-8 | | 5+10x=-49+x | | 5+10x=-49x |